RА discharge dynamics with passing over l- and H-like mode states in the URAGAN-3M torsatron - Chechkin, V.V.; Pankratov, I.M.; Grigor’eva, L.I.; Beletskii, А.А.; Kasilov, A.A.; Burchenko, P.Ya.; Lozin, А.V.; Tsybenko, S.А.; Slavnyj, А.S.; Litvinov, A.P.; Kulaga, А.Ye.; Pavlichenko, R.O.; et al. (Вопросы атомной науки и техники, 2012)
In the l=3 Uragan-3M torsatron a hydrogen plasma with the density ¬ne ~ 2×10¹² cm⁻³ is produced and heated by RF fields in the ω ≤ ωсi range of frequencies with using a frame-like antenna. Time variations are considered of (1) density ne and electron cyclotron emission at different values of the RF power fed to the antenna; (2) fast ion generation and loss; (3) edge electric field Er and edge turbulent transport. Obtained results are of importance for (1) subsequent production and heating of denser plasmas; (2) understanding of processes resulting in the observed transition to the H-like confinement mode. В трехзаходном торсатроне У-3М водородная плазма с плотностью ¬ne ~2×10¹² cm⁻³ создаётся и нагревается ВЧ-полями в области частот ω ≤ ωсi с использованием рамочной антенны. Рассмотрены изменения во времени: 1) плотности ne и электронного циклотронного излучения при различных значениях ВЧ-мощности, подводимой к антенне; 2) генерации быстрых ионов и их потерь; 3) краевого электрического поля Еr и краевого турбулентного пeреноса. Полученные результаты важны для последующего получения и нагрева более плотной плазмы и понимания процессов, приводящих к переходу в Н-подобную моду удержания. У тризаходному торсатроні У-3М воднева плазма зі щільністю ¬ne ~2×10¹² cm⁻³ створюється і нагрівається ВЧ-полями в області частот ω ≤ ωсi з використанням рамкової антени. Розглянуті часові зміни: 1) густини ne та електронного циклотронного випромінювання при різних значеннях ВЧ-потужності, що підводиться до антени; 2) генерації швидких іонів та їх втрат; 3) крайового електричного поля Еr та крайового турбулентного переносу. Одержані результати важливі для подальшого створення та нагріву більш щільної плазми і розуміння процесів, що призводять до переходу в Н-подібну моду утримання.